A nano-optical switch driven by optical force using a laterally coupled double-ring resonator - Cai, H. (2013)
This paper reports a nano-optical switch driven by optical force in a laterally coupled double-ring resonator. The nano-switch consists of two bus waveguides and a double-ring resonator, with one ring suspended. The circulating power in the double-ring resonator generates strong optical force, leading to deformation of the suspended ring. As a result, a resonance shift at the output leads to the switching operation. In experiment, a switching contrast of more than 25 dB is achieved, with a switching time of nano-seconds. Compared with other reported free-carrier effect and/or silicon-based high speed switches, the proposed switch allows switching operation at low pumping power levels in planar nano-scaled structures.